Evaluating and Adapting ELT Materials: Its importance and Implications - Rahmawati, Movi Riana (ENGLISH JOURNAL, 2016)
ELT course books create a range of responses, but are frequently seen by teachers as necessary evils. There seems to be ‘course books credibility gap’ (Grenall, 1984) because of contradictions and potential conflicts of interest in their creation, commercial exploitation and public assessment, selection and ultimate classroom use, ELT books are seen frequently as poor compromises between what is educationally desirable on the one hand and financially viable on the other. Because of that, McDonough and Shaw (2003) state that there are some circumstances that require educators to evaluate their materials. This paper discusses the reasons of adapting and evaluating ELT materials and steps of doing it. It answers the question of what is evaluated, why it is done, who does it, how many types of evaluation there are, and what approaches and tools are used. Then, it also discusses the term adapting and how to do it.